Smart RunnerBot - Tuan Ibrahim, Tuan Mohd Hafeez; Baharun, Hafifa Afiqah; Mohd Rizal, Muhammad Shazwan Khir; Ismail, Suhairi; Kassim, Noraniah (Multidisciplinary Applied Research and Innovation, 2021)
In the present competitive world, it is believed that a lot of human activities will be dominantly automated. There are very few universities in our country that implement this automated system. This project is the very first approach to bring the intelligent and automated system into our university cafeteria. The peak period during lunch break can directly affect the amount of labour required by the cafeteria workers. Each cafeteria operator has a minimum staffing level in order to limit financial constraint. The cafeteria operators may be able to run efficiently with limited workers. Due to this, they may be unable to meet the demands of a high volume of sales during peak hours. This consequently leads to the same workers having to work multiple roles to cater everyone’s needs contributing to poor working performance and reduced productivity. Hence, the main objectives of this project are to develop a smart robot that will help minimize the amount of labour required, boost the productivity of the cafeteria operators and make the targeted university cafeteria a more convenient and technology-friendly environment. In this project, the moving platform is equipped with the aid of Arduino microcontroller with built-in coding, two 15kg load cells with HX711 Amplifier and LED lighting sensor to notify the container is fully-loaded. This moving platform is activated only when the dish container reaches 30kg. Upon activation, it will automatically make it way to the respective cafeteria operators in a fixed route as programmed. Methods used for the study are evaluation of the load distribution of the structure using SolidWorks software. The simulation results and calculation analysis indicate that this project has the capability to serve the purpose with a battery life up to seven hours operation and its main body is able to withstand a maximum burden of 30kg.